Correction: Critical role of deadenylation in regulating poly(A) rhythms and circadian gene expression. - Xiangyu Yao; Shihoko Kojima; Jing Chen (PLoS Computational Biology)
[This corrects the article DOI: 10.1371/journal.pcbi.1007842.].